A practical guide about biosimilar data for health care providers treating inflammatory diseases - Markenson J (Dove Medical Press, 2017)
Joseph Markenson,1,2 Daniel F Alvarez,3 Ira Jacobs,4 Carol Kirchhoff5 1Department of Rheumatology, 2Department of Medicine, Hospital for Special Surgery, New York, NY, 3Pfizer Inc, Collegeville, PA, 4Pfizer Inc, New York, NY, 5Pfizer Inc, Chesterfield, MO, USA Abstract: To make informed decisions about the safety, efficacy, and clinical utility of a biosimilar, health care providers should understand the types and be able to analyze data generated from a biosimilar development program. This article reviews the biosimilar guidelines, the biosimilar development process to provide education and context about biosimilarity, and uses examples from infliximab biosimilars to review the terminology and potential types of analyses that may be used to compare potential biosimilars to the originator biologic. A biosimilar is a biologic product that is highly similar to an approved (originator) biologic, notwithstanding minor differences in clinically inactive components, and with no clinically meaningful differences in terms of the safety, purity, and potency of the product. Due to their complex nature and production in living systems, it is not possible to exactly duplicate the approved originator biologic. To ensure biosimilars provide consistent, safe, and effective treatment comparable to the originator biologic, extensive analyses of the potential biosimilar are conducted, including side-by-side analytical, nonclinical, and clinical comparisons. A key goal is to determine whether there are sufficient relevant similarities in chemical composition, biologic activity, and pharmacokinetic aspects between the potential biosimilar and the originator. Regulatory approvals and marketing authorizations for biosimilars are made on a case-by-case and agency-by-agency basis after evaluating the totality of the evidence generated from the entire development program. Understanding how regulatory agencies review data for approval can help health care providers make appropriate decisions when biosimilars become available for use in the treatment of inflammatory diseases, and therefore they should review the literature to gain further information about specific biosimilars. Keywords: biosimilar, data analysis, inflammatory disease, rheumatoid arthritis